2012
DOI: 10.1097/jcp.0b013e31825d6ddb
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Impairment in Patients Clinically Recovered From Central Nervous System Depressant Drug Overdose

Abstract: Central nervous system depressant drugs (CNS-Ds) are known to impair cognitive functions. Overdose of these drugs is common, and most of the hospital-treated patients are discharged within 24 to 48 hours. No previous studies have examined whether they have residual impairment at the time of discharge. Our aim was to evaluate whether patients with CNS-D overdose are impaired in cognitive domains important in daily activities at that time. We compared visuomotor skills (Trail-Making Test A and Choice Reaction Ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 21 publications
2
15
0
1
Order By: Relevance
“…Our results showed that the CNS-Depressant Group was impaired in all tests in all three 66 domains . After adjusting for confounding factors CNS-Depressant Group was found to be impaired in visual attention and visuomotor skills, executive functions and working memory.…”
Section: O G N I T I V E To X I C I T Y O F S E D a T I V E P S Y Csupporting
confidence: 49%
See 1 more Smart Citation
“…Our results showed that the CNS-Depressant Group was impaired in all tests in all three 66 domains . After adjusting for confounding factors CNS-Depressant Group was found to be impaired in visual attention and visuomotor skills, executive functions and working memory.…”
Section: O G N I T I V E To X I C I T Y O F S E D a T I V E P S Y Csupporting
confidence: 49%
“…The aim of our first study was to determine whether patients with CNS-depressant overdose are cognitively impaired at the time they are clinically deemed fit to be discharged [66][67][68] from hospital .…”
Section: O G N I T I V E To X I C I T Y O F S E D a T I V E P S Y Cmentioning
confidence: 99%
“…Additionally, those experimental results have been confirmed by a clinical study in which patients with CNS depressant drug overdose, especially with BZDs, may be impaired in multiple cognitive functions, especially impaired planning and working memory. Those impairments are under-recognized, and may persist even when patients are considered medically fit for discharge (Dassanayake et al, 2012). Indeed, several studies conducted in this population of BZD self-poisoning patients showed how these or those cognitive impairments, especially anterograde amnesia, can have problematic clinical consequences, because almost half of the patients were unable to recognize the psychiatric resident they had spoken to the day before (Verwey et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Asimismo, algunos estudios en consumidores de esta sustancia han encontrado alteraciones en la impulsividad indicando comportamientos desinhibidos (Michel y Lang, 2003), toma de decisiones impulsivas (Dassanayake et al, 2012;Lane, Tcheremissine, Lieving, Nouvion, y Cherek, 2005), y déficits en la inhibición de respuesta (Acheson, Reynolds, Richards, y de Wit, 2006). Distintos modelos teóricos sobre adicción han señala-do la impulsividad como un marcador de vulnerabilidad de gran relevancia en la explicación de los procesos adictivos, tanto para explicar el inicio como el mantenimiento del consumo de drogas (Adan, 2002, Arce y Santisteban, 2006Cano-Cervantes, Araque-Serrano, y Cándido-Ortiz, 2011;Cortés-Tomás, Giménez-Costa, Motos-Sellés, y Cadaveira-Mahía, 2014;Gullo, Loxton, y Dawe, 2014;Navas, Torres, Cándido, y Perales, 2014;Pattij y De Vries, 2013).…”
Section: Impulsivity In Men With Prescription Of Benzodiazepines and unclassified